2022
DOI: 10.3390/su14127475
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Motivations for Luxury Fashion Rental: A Second-Order Factor Analysis Approach

Abstract: With the rise of the sharing economy, luxury fashion rental (LFR) services have seen significant growth by providing sustainable consumption options to newcomers in the luxury fashion market. Several studies have analysed consumer motivations for luxury and collaborative consumption; however, limited research has examined consumer behaviour towards LFR, focusing on the collaborative consumption perspective but overlooking the influence of the characteristics and values of luxury fashion products. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 89 publications
(193 reference statements)
0
16
0
1
Order By: Relevance
“…Lang and Armstrong, 2018a) and others detecting a positive one (e.g. Ruan et al , 2022). Following the study of Shao et al (2019), we supposed that consumers with high levels of need for distinctiveness desire to express their self-identity through unique products.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…Lang and Armstrong, 2018a) and others detecting a positive one (e.g. Ruan et al , 2022). Following the study of Shao et al (2019), we supposed that consumers with high levels of need for distinctiveness desire to express their self-identity through unique products.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…Prior studies in the context of influential motivations and barriers to fashion rentals are illustrated in Table 1. Aspects such as affordability (Park & Lee, 2022; Ruan et al, 2022), showing possessions in social settings (Jain & Mishra, 2019; Mishra et al, 2022), self‐expression (McNeill & Venter, 2019), desire to differentiate (Lang & Armstrong, 2018; Ruan et al, 2022), trial of new styles (Bodenheimer et al, 2022; Park & Lee, 2022), environmental friendliness (Bodenheimer et al, 2022; Ruan et al, 2022), convenience (Park & Lee, 2022), smarter shopping (Ruan et al, 2022), product life extension (Pantano & Stylos, 2020), wide variety (Lee et al, 2021), user‐friendly digital platforms (Lang et al, 2020; Park & Armstrong, 2019), rental business proficiency, trust in the rental firm, personal data protection (Fota et al, 2019), a sense of fun (Ruan et al, 2022; Baek et al, 2021), creativity and change (Park & Lee, 2022), ego defence (Ruan et al, 2022), novelty and quality preferences (Helinski & Schewe, 2022), wardrobe transformation (Neerattiparambil, 2020), fashion leadership, social media usage, price consciousness (Myin et al, 2022), perceived consumer effectiveness, perceived individual relevance (Chi et al, 2023), quality service (Krishnakumar, 2023), fit, and occasion aptness (McKinney & Shin, 2016) are perceived motivations to renting fashion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Finland, researchers found that rental service-systems are best suited for young-consumer, because of its experiential, innovative and social characteristics (Armstrong et al, 2015). Additionally, some researchers focused on the luxury fashion segment within online rentals (Ruan and Xu, 2018;Mishra et al, 2021) or baby clothes (Petersen and Riisberg, 2017).…”
Section: The Current State Of Research On Consumer Attitude Toward Re...mentioning
confidence: 99%